2007
DOI: 10.1152/ajpcell.00588.2005
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin-NFATc signaling pathway regulates AQP2 expression in response to calcium signals and osmotic stress

Abstract: December 13, 2006; doi:10.1152/ajpcell.00588.2005.-The aquaporin (AQP)2 channel mediates the reabsorption of water in renal collecting ducts in response to arginine vasopressin (AVP) and hypertonicity. Here we show that AQP2 expression is induced not only by the tonicityresponsive enhancer binding protein (TonEBP)/nuclear factor of activated T cells (NFAT)5-mediated hypertonic stress response but also by the calcium-dependent calcineurin-NFATc pathway. The induction of AQP2 expression by the calcineurin-NFATc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
76
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 45 publications
7
76
1
Order By: Relevance
“…In T cells and kidney cells, there is some evidence to indicate that regulation may be mediated by a phosphatase, Cn, which is activated by calcium ions (24,25). The results of the studies described herein suggest that this mechanism may be cell type-specific.…”
Section: Discussionmentioning
confidence: 75%
“…In T cells and kidney cells, there is some evidence to indicate that regulation may be mediated by a phosphatase, Cn, which is activated by calcium ions (24,25). The results of the studies described herein suggest that this mechanism may be cell type-specific.…”
Section: Discussionmentioning
confidence: 75%
“…Li et al (14) reported that the effect of hypertonicity on AQP2 transcription depends on NFATc sites in the AQP2 promoter. The NFATc sites tested by Li et al are localized in segments 1, 6, and 7 of the Ϫ0.4 kb promoter.…”
Section: Discussion Mpkccd Cells Are a Proper Model To Study Tonicitymentioning
confidence: 99%
“…This protein is up-regulated with hyperto-nicity in cultured cells and in the kidney medulla (11,12) and TonEBP knockdown or inhibition, but also mutation of its tonicity-responsive element (TonE) in the AQP2 promoter, reduced AQP2 expression in mpkCCD cells (13,14). Moreover, in TonEBP Ϫ/Ϫ mice and mice transgenic for dominant-negative TonEBP, AQP2 expression was decreased (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NFATc transcription factors are extensively studied calcineurin substrates and are major regulators of transcription in response to Ca 2+ / calcineurin signals (11,43). Upon activation by increased intracellular Ca…”
Section: +mentioning
confidence: 99%